Idiopathic ileoileal intussusception without lead point in a 4-year-old child - Koç, Ayşe Selcan; Özçelik, Zerrin; Görgülü, Feride Fatma (The European Research Journal, 2018)
Intussusception is common abdominal emergency in early childhood. Idiopathic ileoileal intussusceptions are rare in children without an apparent predisposing cause. Patients present with vomiting and colicky abdominal pain, which can mimic many conditions. We report a case with primary ileoileal intussusception, which was successfully reduced manually during exploratory laparotomy. There was no evidence enlarged mesenteric lymph nodes.